Salivary gland function in thyroid cancer patients with radioiodine administration history - Krcalova, Eva; Horacek, Jiri; Gabalec, Filip; Zak, Pavel; Dolezal, Jiri (Biomedical papers, 2020)
Aim: Radioiodine (RAI) improves survival in patients with locally advanced or metastatic differentiated thyroid carcinoma (DTC). Although there has been an ongoing debate on RAI-induced salivary gland damage, published data have been inconsistent. Therefore, the purpose of our study was to compare salivary gland function in intermediate and high risk DTC patients after single or repeated RAI treatment with their age- and sex-matched RAI-naive counterparts. Methods: Uptake and excretion of parotid and submandibular glands were quantitatively evaluated using 99mTc-pertechnetate salivary gland scintigraphy in 23 patients previously treated with RAI. Patients (median 9.25 GBq 131I-NaI; Q1-Q3: 5.55-16.65; range: 5.55-27.5) were divided into subgroups according to previously administered 131I-NaI activity using cut-off values 5.55 GBq and 9.25 GBq. Their salivary gland scintigraphy results were compared with RAI-naive patients using Mann-Whitney test. Results: Compared to RAI-naive patients, parotid glands pertechnetate uptake was significantly lower in those treated with > 9.25 GBq (P=0.034) and parotid glands excretion fraction was already decreased with RAI activities > 5.55 GBq (P=0.031). In submandibular glands, no statistically significant difference in either function was observed even with RAI activity > 9.25 GBq. Conclusion: Our data suggest that RAI therapy using activities ≤ 5.55 GBq does not substantially decrease saliva production. Activities > 5.55 GBq may lead to significant decrease in parotid excretion, and activities > 9.25 GBq also diminish parotid uptake. Surprisingly, submandibular glands, providing majority of seromucinous saliva under basal condition, seem to be unaffected even by RAI activities above 9.25 GBq.
Keywords: radioiodine; thyroid cancer; salivary gland dynamic scintigraphy; 99mTc-pertechnetate